Atributos de la empresa como elementos diferenciadores de la imagen corporativa. Caso: Tigre Ecuador S.A. - Cordero Loyola, Ana Elizabeth (2016)
The development of this research has as main objective the creation of a communication plan, whose main objective is oriented to the proposed communication strategies seeking to publicize the attributes of the company Tigre Ecuador S.A. as differentiators corporate image. To this end, it is essential to consider the study and analysis of these attributes, which will diagnose the current situation of your corporate image and strengthen it. Thus, the approach of both strategies and specific actions for this proposal have been made after a literature study; in addition to the implementation and analysis of surveys and interviews applied to dealers and customers of the organization; who will become the main beneficiaries of the determination of the differentiating factors of the corporate image of Tiger Ecuador, since it is responsible for apply, solidify and improve them. Naturally, following this investigation it was found that the investigated attributes such as product quality, infrastructure, variety and price differentiators are well regarded by the respondent target audience; however, confidence in the organization is not entirely strengthened, since few people who recognize the organization and its brand, while still less those who are truly faithful to the acquisition of the products offered by Tigre Ecuador. It is therefore essential to understand that is to improve and correct strengthening of the distinctive attributes of Tiger Ecuador, essential to consider the corporate communication as an element of management of them, as it seeks to inform the various stakeholders through ommunication tools with which the entity has, claiming the existence of an ideal relationship between what differentiates the organization and what it communicates through if corporate image.